SUSTAINING FAMILY HARMONY AMIDST THE KHURUJ PRACTICES OF THE JAMAAH TABLIGH IN CENTRAL LOMBOK - Amri, Khairul; Ratna Mulhimah, Baiq; Muhammad Nurul Wathani, Lalu (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2025)
This study examined the influence of khuruj practices on family harmony within the Jamaah Tabligh community in Central Lombok Regency. Khuruj, as a form of da'wah involving leaving home for a certain period of time, creates unique dynamics within family relationships, particularly regarding economic responsibilities, child and spouse nurturing, and the maintenance of domestic harmony. This study employs a qualitative approach with field research as its research method. Data collection techniques include observation, in-depth interviews with twelve informants, and documentation with informants comprising members of the Tabligh Jamaah family, community leaders, and religious figures in Central Lombok. The research findings reveal that harmony within the households of Jamaah Tabligh families in East Lombok Regency is achieved through three key strategies: (1) establishing open communication between spouses as the foundation of the relationship, (2) agreeing on the time and duration of khuruj in a proportional manner, and (3) optimizing the role of the wife as the guardian of household balance. This study provides insights into the importance of communication and collaboration within Tabligh Jamaah families to achieve harmony in economic responsibilities and child upbringing. The wife's role as a supporter of family stability and agreements regarding khuruj time are key to reducing tension within the household. Thus, this study can serve as a reference for families in managing social and economic dynamics and strengthening family resilience.